Marine carotenoids: Bioactivities and potential benefits to human health. Issue 12 (13th August 2017) - Chuyen, Hoang Van; Eun, Jong-Bang
ABSTRACT: Among natural pigments, carotenoids play important roles in physiological functions. The characteristics of carotenoids and their effects on human health have been reported for a long time, but most studies have focused on carotenoids from vegetables, fruits, and other parts of higher plants. Few reports are available on carotenoids from marine sources, such as seaweeds, microalgae, and marine animals, which have attracted attention in recent decades. Hundreds of carotenoids have been identified and isolated from marine organisms and their beneficial physiological functions, such as anticancer, antiobesity, antidiabetic, anti-inflammatory, and cardioprotective activities have been reported. The purpose of this review is to discuss the literature on the beneficial bioactivities of some of the most abundant marine carotenoids, including fucoxanthin, astaxanthin, cantaxanthin, peridinin, fucoxanthinol, and halocynthiaxanthin.